2009
DOI: 10.1055/s-0029-1211795
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of plasma endothelin-1 in non-insulin dependent diabetic patients with retinopathy but without other diabetes-related organ damage

Abstract: Increased levels of endothelin (ET-1), a potent endothelium-derived vasoconstrictive peptide, have been found in plasma from non-insulin dependent diabetic (NIDDM) patients, suggesting that ET-1 might represent a new marker of diabetes-related vascular damage. To elucidate this topic, circulating ET-1 levels were evaluated in 16 NIDDM patients in good metabolic control without either cardiovascular risk factors (obesity, hypertension, smoking, hyperdislipidaemia, etc.) or diabetes-related damage of other distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…In contrast, other researchers observed increased plasma IR-ET-1 levels in type 2 diabetes with retinopathy. 38,39 Nevertheless, the plasma IR-ET-1 levels do not seem to contribute significantly to the increased vitreous IR-ET-1 levels in patients with PDR.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, other researchers observed increased plasma IR-ET-1 levels in type 2 diabetes with retinopathy. 38,39 Nevertheless, the plasma IR-ET-1 levels do not seem to contribute significantly to the increased vitreous IR-ET-1 levels in patients with PDR.…”
Section: Discussionmentioning
confidence: 96%
“…have shown that the increased levels of ET-1 could contribute to retinopathy development or, more probably, represent a marker of this diabetes-related complication. [37]…”
Section: Circulating Biomarkers In Diabetic Retinopathymentioning
confidence: 99%
“…Indeed, a positive correlation was reported for DR and cardiovascular inflammatory factors, highlighting that strategies focused to decrease inflammatory activity may prevent the development of vascular complications in type 1 diabetes (Schram et al, 2005). Of interest, increased plasma levels of Endothelin (ET-1), a potent endothelium-derived vasoconstrictive peptide, have been found in non-insulin-dependent diabetic (NIDDM) patients, prospecting ET-1 as new marker of vascular damage in diabetic subjects (Laurenti et al, 1997). Jacqueminet and coworkers proposed the peripheral blood MMP-9 levels as "a suitable substitute biomarker" of retinopathy in type-1 diabetes not associated with vascular complications (Jacqueminet et al, 2006).…”
Section: Biomarkers In Drmentioning
confidence: 99%